Appraisal Analysis on Thailand Advertisement - Linda Wijaya; Afrida Hanum; Nena Syahrani Syahaf Nasution (Politeknik Negeri Padang, 2019)
Communication occurs when one can express his/her opinion, thought, idea on people, things and situations. Opinion-related meanings in language are regarded as resources of evaluation or appraisal in language. Not necessarily good or bad in a moral sense, attitude accompanies the language utterance every person utters. As one kind of appraisal resources, attitude plays an important role in the expression of interpersonal meanings of language. Attitude refers to a way that you behave towards someone or in a particular situation, especially when this shows how you feel.The aims of this study are to analyze five advertisements in terms of content and to look deeply into the language employed in the discourse of advertisement as well as to find out the Appraisal elements used by Thailand advertisers especially to promote their product and reach the target. In This study, it is found that judgment and affect are appraisal element that most used in Thailand Advertisement because judgment is used to evaluate human behavior towards the product, and affect is used to evaluate the benefit or advantage in the product.